Generation of counterpropagating and spectrally uncorrelated photon-pair states by spontaneous four-wave mixing in photonic crystal waveguides - Saravi, Sina; Zhang, Yu; Chen, Xiao; Afsharnia, Mina; Setzpfandt, Frank; Pertsch, Thomas (Frontiers in Photonics, 2022)
In this work, we propose and theoretically analyze a new scheme for generation of counterpropagating photon pairs in photonic crystal waveguides through the process of spontaneous four-wave mixing. Using the fundamental properties of periodic Bloch modes in a standard photonic crystal waveguide, we demonstrate how modal phase-matching can be reached between forward-propagating pump modes and counterpropagating signal and idler modes, for generation of degenerate and non-degenerate photon pairs. We then show how this scheme can be used for generation of photon pairs that are nearly uncorrelated in the spectral degree of freedom. Such a source will be highly interesting as a heralded source of single photons, especially as the spectrally separable signal and idler photons are also spatially separated directly at the source. We conduct our investigation based on a design in silicon, yet our design concept is general and can in principle be applied to any nanostructured material platform.